2020
DOI: 10.31234/osf.io/x5upn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rock ’n’ Roll but not Sex or Drugs: Music is negatively correlated to depressive symptoms during the COVID-19 pandemic via reward-related mechanisms

Abstract: The COVID-19 pandemic has deeply affected mental health. We assessed which of many leisure activities had positive psychological effects, with particular attention to music, which has been reported anecdotally to be important. Questionnaire data from over a thousand individuals primarily from Italy, Spain, and the USA during spring 2020 show that people picked music most often as the best activity to cope with psychological distress. Hours of engagement in music and food-related activities during the pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 75 publications
6
44
0
Order By: Relevance
“…Moreover, since the invitation to participate in the study mentioned we were interested in the effect of daily activities "especially music" on wellbeing goals, our sample may have been biased toward those with a special affinity for music. Nonetheless, our results are totally consistent with a recent study showing the superiority of music listening in obtaining wellbeing goals over other activities, during the COVID-19 pandemic, in a different sample not especially inclined toward music (Mas-Herrero et al, 2020).…”
Section: Limitations and Future Directionssupporting
confidence: 92%
“…Moreover, since the invitation to participate in the study mentioned we were interested in the effect of daily activities "especially music" on wellbeing goals, our sample may have been biased toward those with a special affinity for music. Nonetheless, our results are totally consistent with a recent study showing the superiority of music listening in obtaining wellbeing goals over other activities, during the COVID-19 pandemic, in a different sample not especially inclined toward music (Mas-Herrero et al, 2020).…”
Section: Limitations and Future Directionssupporting
confidence: 92%
“…This suggests that during lockdown, reminders of people resulting from musicevoked nostalgia may be independent from the degree of valence induced by the music. A possible interpretation of this finding is that reminders of people through music are prevalent due to the separation caused by lockdown, as was found in several recent studies of the role of music during the pandemic for social surrogacy (Mas-Herrero et al, 2020;Fink et al, 2021;Granot et al, 2021). However, any specific emotion evoked by musicevoked nostalgia did not arise as a result of being reminded of people they may have been separated from, but from other variables such as appreciating the past, or acknowledgment of happy past times or sad difficult times.…”
Section: Research Question 1: Frequency Of Listening and Narrative Amentioning
confidence: 56%
“…Globally, music has held prominence in facilitating social connectedness and emotion regulation in response to COVID-19 (Granot et al, 2021). Individuals have selected music as means to cope with psychological distress, which has served as important means for improving wellbeing (Mas-Herrero et al, 2020), and cope with periods of social isolation (Krause et al, 2021). For those who have experienced an increased negative mood as a result of the pandemic, music listening has helped them to cope emotionally, and regardless of changes in emotions, music has provided a sense of social connectedness for all (Fink et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The same report found dramatic surges in video-based services (e.g., YouTube). Some platform-neutral, self-report measures indeed suggest increased music listening during lockdown (Cabedo-Mas et al, 2020;Fink et al, 2021;Mas-Herrero et al, 2020;see, however, Krause et al, 2020). Qualitative findings support these lifestyle-related changes in music consumption, including the switch to video-based streaming (Carlson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Across 11 countries, Granot et al (2021) found that musical engagement provided the most effective, physically distanced leisure activity for achieving wellbeing goals. Mas-Herrero et al (2020) showed that people in Italy, Spain, and USA picked music-related activities over entertainment (e.g., watching series, movies, reading books) and physical exercise as the most helpful coping mechanism for pandemic-induced distress. The hours spent on musical activities during (but not before) lockdown were negatively associated with anxiety and depression, and this effect was mediated by individual reward sensitivity.…”
Section: Introductionmentioning
confidence: 99%